The state of health infrastructure investments in the Philippines and assessment of the Health Facility Enhancement Program (HFEP) - Therese Jules P. Tomas; Danielle Lois M. Carreon; Louie Iyar L. Dagoy; Aaron Carlos G. Manuel; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2025)
The Health Facilities Enhancement Program (HFEP) is a capital investment grant administered by the Department of Health (DOH), designed to help local government units (LGUs) augment their health infrastructure, such as primary healthcare facilities, hospitals, and equipment. Over the past decades, HFEP has accounted for approximately 12% of DOH's total budget. Despite its scale and over a decade of implementation, systematic program evaluations remain limited. We used a mixed-methods approach to assess the various stages of program implementation: planning, budget allocation, execution, and monitoring and evaluation. At each stage, we identify critical challenges undermining the program's effectiveness. Our findings reveal long-standing inequities in grant distribution, with some LGUs receiving national funding despite not being among those with the greatest need. This study aims to provide insights to inform supply-side reforms, ensuring a more equitable and efficient allocation of national resources in a highly decentralized health system.
Keywords: 330; Health Facilities Enhancement Program; health infrastructure; health capital expenditure; capital stock; health facilities; equipment